Numerical simulation on the optimisation of directed energy deposition process - Teo, Bryan Jie Chao (Nanyang Technological University, 2022)
Composed in 1997, Directed Energy Deposition (DED) has since revolutionised the way 3D objects are printed, with modern additive manufacturing methods taking the lead in precision engineering and smart computing capabilities. Optimisation of critical process output requires the command of strategic steps approach in the utilization of engineering software providing real-time simulation data. As such, the optimisation of DED process is still an ongoing process and further research are conducted in studying the flow parameters and its performance metrices. In this study, investigations are done to determine the maximum distance of powder flow convergence (Focal Point Height) measured from the nozzle exit up to the focal point of the nozzle outlet in a DED additive manufacturing process. In addition, the size of the powder beam (Focal Point Width) was also measured to determine the spread of the maximum powder concentration along the nozzle outlet. A 3D design and engineering simulation software (Ansys) was used to simulate the powder flow with both fluid gas velocity and powder concentration measured at the end of the simulation process. Various parameters such as the primary and secondary inlet gas flow rate, as well as the powder mass flow rate are applied under nine different conditions to obtain a diversified set of results. The results gathered from both simulation and experimental processes indicate a significant difference in focal point height and width which was accentuated by modification in nozzle design geometry.